Phenotyping of a novel COL4A4 and novel GLA variant in a patient presenting with microhematuria and mildly impaired kidney function: a case report - Ponleitner, Markus; Allmer, Daniela Maria; Hecking, Manfred; Gatterer, Constantin; Graf, Senta; Smogavec, Mateja; Laccone, Franco; Rommer, Paulus Stefan; Sunder-Plassmann, Gere (Frontiers in Genetics, 2023)
We describe the case of a 44-year-old male patient with a longstanding history of microhematuria and mildly impaired kidney function (CKD G2A1). The family history disclosed three females who also had microhematuria. Genetic testing by whole exome sequencing revealed two novel variants in COL4A4 (NM_000092.5: c.1181G>T, NP_000083.3:p.Gly394Val, heterozygous, likely pathogenic; Alport syndrome, OMIM# 141200, 203780) and GLA (NM_000169.3: c.460A>G, NP_000160.1: p.Ile154Val, hemizygous, variant of uncertain significance; Fabry disease, OMIM# 301500), respectively. Extensive phenotyping revealed no biochemical or clinical evidence for the presence of Fabry disease. Thus, the GLA c.460A>G, p.Ile154Val, is to be classified as a benign variant, whereas the COL4A4c.1181G>T, p.Gly394Val confirms the diagnosis of autosomal dominant Alport syndrome in this patient.